Reliability Measure Model for Assistive Care Loop Framework Using Wireless Sensor Networks. Issue 2 (2010) - Balasubramanian, Venki; Hoang, Doan B.
Abstract : Body area wireless sensor networks (BAWSNs) are time-critical systems that rely on the collective data of a group of sensor nodes. Reliable data received at the sink is based on the collective data provided by all the source sensor nodes and not on individual data. Unlike conventional reliability, the definition of retransmission is inapplicable in a BAWSN and would only lead to an elapsed data arrival that is not acceptable for time-critical application. Time-driven applications require high data reliability to maintain detection and responses. Hence, the transmission reliability for the BAWSN should be based on the critical time. In this paper, we develop a theoretical model to measure a BAWSN's transmission reliability, based on the critical time. The proposed model is evaluated through simulation and then compared with the experimental results conducted in our existing Active Care Loop Framework (ACLF). We further show the effect of the sink buffer in transmission reliability after a detailed study of various other co-existing parameters.